2009
DOI: 10.1097/opx.0b013e318196a74b
|View full text |Cite
|
Sign up to set email alerts
|

Care Regimen and Lens Material Influence on Silicone Hydrogel Contact Lens Deposition

Abstract: Lens polymer (possibly associated with surface characteristics) is a prominent factor affecting lipid and protein accumulation. Within a lens polymer type, lens care solutions exhibit varying effectiveness in reducing protein and lipid accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 35 publications
6
57
1
Order By: Relevance
“…This also confirms prior studies that reported that lotrafilcon B materials sorbed less lipid than balafilcon A materials in worn lenses 5,8 and also in lenses incubated in vitro. 12 Lorentz et al 9 performed a similar study with lenses incubated in ATF; they found approximately 1/6 to 1/10 the sorption on balafilcon A than we report herein.…”
Section: Sorption On Four Commercial Lensessupporting
confidence: 93%
“…This also confirms prior studies that reported that lotrafilcon B materials sorbed less lipid than balafilcon A materials in worn lenses 5,8 and also in lenses incubated in vitro. 12 Lorentz et al 9 performed a similar study with lenses incubated in ATF; they found approximately 1/6 to 1/10 the sorption on balafilcon A than we report herein.…”
Section: Sorption On Four Commercial Lensessupporting
confidence: 93%
“…MPSs can vary in their efficiency with differences in their composition, manufacturer, and cleaning and storage times. 22,30 While the staining results for the MPS control lenses were similar to those found after exposure to ATF, the rationale for the results is very different. In this instance, MPS components associate with the lens HDs in an attempt to block biofouling, thus also decreasing the binding sites for staining.…”
Section: Discussionmentioning
confidence: 71%
“…1 Lotrafilcon A, on the other hand, uses a plasma coating treatment that coats the lens surface with a 25-nm thick hydrophilic polymer. 21,22 Galyfilcon A (Acuvue Advance; Johnson & Johnson Vision Care, Jacksonville, FL) and senofilcon A (Acuvue Oasys; Johnson & Johnson Vision Care) do not utilize such techniques, but rather use internal wetting agents to increase hydrophilicity. 21 Current methodologies to determine the hydrophobicity of contact lens surfaces are limited to surface energy measurements such as captive bubble, sessile drop, and Wilhelmy plate contact angles.…”
Section: Purposementioning
confidence: 99%
“…6,7 Ex vivo, free cholesterol and phospholipids have been identied and quantied on a range on silicone hydrogel lens formulations. 3,8 Importantly however, recent characterization of the tear lipidome suggests that free cholesterol and phospholipids are only minor components of the endogenous tear lm.…”
Section: Introductionmentioning
confidence: 99%
“…These deposits are primarily composed of lipids and protein adsorbed from the tear lm and corneal surface. 3,4 Extensive studies have identied and quantied the protein components of these deposits, and recent reports demonstrated that the proles of protein deposition are dependent on contact lens formulation. 3,5 In contrast, limited information is available regarding the lipid composition of deposits on silicone hydrogel contact lenses.…”
Section: Introductionmentioning
confidence: 99%